A Cross-sectional Study of Immune Seroconversion to SARS-CoV-2 in Frontline Maternity Health Professionals. Issue 4 (22nd December 2021) - Bampoe, S.; Lucas, D.N.; Neall, G.; Sceales, P.; Aggarwal, R.; Caulfield, K.; Siassakos, D.; Odor, P.M.
Abstract : ( Anaesthesia . 2020;75:1614–1619) Seroconversion rates for COVID-19 provides data on the pervasiveness and spread of the infection. One challenge is the rate of asymptomatic seroconversion. This has implications for health care providers on the frontline of obstetric care, who may be at increased risk of COVID-19 transmission to and from patients and staff. To date, there are no studies that have provided a baseline rate of seroconversion in frontline, obstetric care providers. The aim of this study was to assess the prevalence of seroconversion in obstetric providers who were not previously diagnosed with SARS-CoV-2 and examine the associations among their characteristics, symptoms, and seroconversion.